Serum CEA, CA19-9, and AFP as Biomarkers for Gastric Cancer: AFP, CEA, CA19-9 in gastric cancer - Wu, Zhonghua; Zhang, Fanyong (Journal of Medical Biochemistry, 2025)
Background: The diagnostic value of AFP, CA19-9 and CEA as biomarkers in gastric carcinoma remains uncertain. This research explores their role in forecasting patient survival and disease progression.  Methods: A total of 630 early-stage gastric cancer patients who underwent gastrectomy between January 2018 and June 2024 were analyzed. Pathological evaluations were conducted, and serum concentrations of CEA, CA19-9, and AFP were measured. Statistical methods were applied to assess the relationship between these markers, tumor characteristics, and their impact on prognosis.  Results: The mean age of patients was 59 years. The 1-year and 5-year survival rates were 98.3% and 91.4%, respectively. The positivity rates for CEA, CA19-9, and AFP were 5.1%, 6.2%, and 2.3%, respectively, resulting in an overall detection rate of 12.4%. Elevated levels of CEA and CA19-9 were associated with metastasis of lymph node and higher tumor stages, while AFP showed no meaningful association with disease characteristics. Multivariate analysis identified age over 65, lymph node metastasis, and high CEA levels as independent risk factors for poorer outcomes in gastric cancer.Conclusions: Although CEA, CA19-9, and AFP individually show low detection rates in gastric cancer, their combined use improves diagnostic accuracy. Elevated CA19-9 is associated with lymph node metastasis, and high CEA independently indicates a poorer prognosis. Additional research is necessary to clarify the clinical utility of these biomarkers in early detection and prognostic evaluation.
Keywords: Tumor markers, AFP, CA19-9, CEA, clinical significance, gastric cancer, survival analysis